PENYELESAIAN SENGKETA ANTARA KONSUMEN DAN PELAKU USAHA OLEH BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK) KOTA PADANG SECARA ARBITRASE (Perkara Konsumen Nomor : 11/P3K/IV/2019) - Amelia Anggraini Fitri dan Yunimar (Normative Jurnal Ilmiah Hukum, 2021)
Every time people interact with each other and this interaction often results in disputes or disputes between these parties. The disputing parties will find a way to resolve the dispute. The method of dispute resolution that we are familiar with is the method of resolving the dispute (court) and non-litigation (outside the court). The agency officially by the government to resolve disputes between consumers and business actors is the Consumer Dispute Resolution Agency. One of the duties and authorities of BPSK in the Decree of the Minister of Industry and Trade of the Republic of Indonesia Number: 350 / KPP / Kep / 12/2001 concerning the Implementation of Duties and Authorities of BPSK, namely BPSK can resolve consumer cases through arbitration. From the results of the research, it was obtained that the arbitration conducted at the BPSK of Padang City was different from the arbitration regulated in Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. BPSK in proceedings is regulated in the Decree of the Minister of Industry and Trade of the Republic of Indonesia Number: 350 / KPP / Kep / 12/2001 concerning the Implementation of Duties and Authorities of BPSK. Constraints in resolving consumer disputes are caused by 2 factors, namely internal factors and external factors. Internal factors consist of an incomplete library, lack of training for the Council, lack of facilities and infrastructure, as well as external factors that come from the community who are not responsive to the BPSK of Padang City. The solution provided by BPSK Kota Padang is that the Assembly looks for other literary materials from the internet and takes part in trainings.